Are missed appointments in an outpatient clinic for adults with congenital heart disease the harbinger for care gaps?. (3rd May 2021) - Goossens, Eva; van Deyk, Kristien; Budts, Werner; Moons, Philip
Abstract: Aims: Life-long follow-up is vital for patients with congenital heart disease (CHD) to safeguard longevity. Missing scheduled appointments might be prodromal to subsequent care gaps, but our understanding of their occurrence and impact is limited. This study determined the occurrence and predictors of missed appointments (MA), assess its predictive value for care gaps, and explored if MA or care gaps are associated with increased mortality. Methods and results: From 2007 to 2009, the occurrence of MA in 2075 CHD patients was documented at an adult CHD clinic. The frequency of outpatient visits in 1363 adults with moderate to complex CHD was calculated from 2009 to 2012. Patients without a visit were considered to have a care gap. Data on mortality were collected from 2013 to 2017. Missed appointments occurred in 11% of patients and were more common in men [odds ratio (OR) = 1.57; 95% confidence interval (CI): 1.18–2.08], without a history of cardiac procedures (OR = 1.46; 95% CI: 1.08–1.97), and for morning visits (OR = 1.45; 95% CI: 1.10–1.92). Care gaps were identified in 6% of moderate to complex CHD. A MA was significantly associated with an increased likelihood of care gaps (OR = 19.55; 95% CI: 11.92–32.07; R 2 = 26.5%). In moderate to complex CHD, no difference in mortality rates was related to the occurrence of discontinued care. Conclusion: The occurrence of MA was related to patients' gender, no history of cardiac interventions, and time of day of the outpatient visits. Care gaps were associated by the preceding MA. No association with increased mortality rates was observed. Interventions reducing missed appointments, such as SMS-reminders prior to visits, need investigation.